POLITIK LUAR NEGERI INDONESIA DALAM MEWUJUDKAN POROS MARITIM DUNIA PADA ERA PEMERINTAHAN PRESIDEN JOKO WIDODO - Mohammad Maiwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2017)
This study aims to analyze of the foreign policy of Indonesia in realizing the axis of maritime world under the President Joko Widodo. The method used is descriptive analysis with qualitative approach. The result of study shows that Indonesia foreign policy in realizing axis maritime is based on factual and strategic aspects. The strategy pursued by the government is through maritime diplomacy in the form of maritime economic and maritime defense diplomacy. Other than that efforts to realize the axis maritime is done through enhanced regional cooperation and participation in regional, multilateral, and global forums. The policy is integrally followed by the development of the maritime sectors that includes; strenghening connectivity, the development of local and coastal economic, blue and marine economic, fisheries sea transportation, and maritime industry.